Lekarz szuka pacjenta. Leksyka wartościująca pozytywnie na internetowych stronach gabinetów stomatologicznych - Michalska, Beata (Poznańskie Spotkania Językoznawcze, 2014)
Modern business is connected with the Internet, and—on the background of the prototypic corporate Web sites—the pages of doctors’ offices constitute a separate category as the advertising of medical services in Poland is regulated by law. Because of that, doctors—being the owners of private surgeries—are confronted with significant limitations in this area. According to the Act of the Supreme Medical Council (Pol. Naczelna Rada Lekarska) of December 16, 2011 doctors are not allowed to advertise the health services they provide. It is permitted to publish only the information including, among others, the professional title, specialization, the name and surname, days and hours of admission, with the reservation that such information may not possess the attributes of an advertisement. Practically, it is very hard to discern the difference between information and advertisement. The survey of the Web sites of dental offices indicates the presence of communicative elements fulfilling the persuasive function. More careful reading allows one to notice also the evaluating lexis. The compiled research material allows the author to suggest a hypothesis that the studied texts represent persuasive acts of speech.